APLIKASI PEMBELIAN DAN PENJUALAN PADA TOKO SEMBAKO BILHIL - Anwar, Sifaul; Sudrajat, Ari; Rohmah, Neng Ela Siti (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2023)
This study aims to analyze, design, implement and test the purchase and sales application at Toko Sembako Bilhil. The research methodology used is descriptive method and waterfall development The implementation of purchase and sales application uses Microsoft Visual Studio 2017 Community programming language and MySQL database. As for testing the system using Black Box Testing. The purchase and sales application designed and implemented at Toko Sembako Bilhil can be a solution to the problems that exist in the system used by Toko Sembako Bilhil in the recording process in order to obtain effective and efficient record purchase and sales information. This system has access rights that can be set when logging in which serves to protect data security. So when displaying the main menu will be in accordance with the Access authority that the user has. From the results of black box testing that has been done, it can be concluded that the system with features in the application ranging from data input, process and produce report as the output works well.